Hubungan Antara Konsumsi Makanan Junkfood dengan Obesitas pada Kalangan Remaja di Kabupaten Deli Serdang - Sari Malem br Ginting; Henny Henny; Dewi Fibrini (Jurnal Pendidikan Indonesia, 2025)
Obesity is a very worrying problem, especially for teenagers, because obesity can reduce self-confidence in some teenagers, thereby disturbing the psychology of teenagers. The main factor causing obesity in teenagers is excessive food intake, whether from ready-to-eat processed foods, fizzy drinks or snacks such as junk food. The aim of this research is to analyze the relationship between junk food consumption and obesity among teenagers in Deli Serdang district. The type of research used in this research is observational quantitative research using a cross-sectional research design. Sampling in this study used the Rao Purba formula because the exact population size is unknown, while the sample size was 97 respondents. The data analysis used is univariate and bivariate analysis. The results showed that the majority of respondents in this study were 16-18 years old, 63 (64.9%), and 54 (55.7%) were female, the majority of respondents in this study often consumed junk food, namely 75 respondents (77 .3%), the majority of respondents in this study were obese in the mild category, 46 respondents (47.4%), there was a relationship between junk food consumption and obesity among teenagers in Deli Serdang district P - Value < 0.05.